Motivasi Belajar Mahasiswa pada Mata Kuliah Manajemen Keperawatan menggunakan Metode Student Centered Learning: Penelitian Kuasi Eksperimen - Rejeki, Yunita Fitri; Wahyudin, Tantowi Purnama; Erawan, Annisa Nur (PT Karya Inovasi Berkelanjutan, 2025)
Introduction and MethodsThe Student-Centered Learning (SCL) method is a learning approach that positions students as active participants in the learning process. This study aimed to examine the effect of implementing the SCL method in the Nursing Management course in the Undergraduate Nursing Program. A quasi-experimental design with a one-group pretest–posttest design was employed, involving 144 students as respondents. The respondents were divided into five groups across different levels. During the Nursing Management course, each group received learning through SCL methods based on role-play and simulation in accordance with the course topics. In the first week, a pretest using a learning motivation questionnaire was administered to assess the respondents’ initial conditions. After the completion of the course series, a posttest using the same instrument was conducted in the final week to measure changes in learning motivation. Data were collected using a validated questionnaire and analyzed through frequency distribution. ResultsThe findings revealed that the majority of respondents were female (76.39%) and perceived the implementation of the SCL method as fairly effective in enhancing understanding, skills, and active participation in the learning process. Conclusion and RecommendationsThese findings are consistent with previous studies indicating that the SCL method can improve learning independence, critical thinking skills, and students’ communication abilities. However, challenges remain in its implementation, particularly concerning the readiness of lecturers and students to manage time and learning resources. Therefore, the SCL method can be considered a relevant learning strategy to enhance the quality of nursing education, although continuous support in the form of training and periodic evaluation is necessary.